2014
DOI: 10.1111/ijpo.279
|View full text |Cite
|
Sign up to set email alerts
|

Fatty liver disease, glucose tolerance and insulin resistance in obese adolescents

Abstract: This study provides no support to the notion that intra-hepatic fat has a role in the regulation of fasting blood glucose, 2-h postprandial blood glucose or systemic insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Our study participants performed a similar exercise stress of 5 x 30‐s bouts of quadriceps exercise (total exercise time: 2.5 min), however, at a significantly higher percentage of their peak capacity (65% versus 30%). Slyper and colleagues have also revealed that adiposity, visceral fat volume in particular, is the sole predictor of insulin resistance in obese adolescents ; therefore, it clearly remains a challenge to dissociate the relationship between obesity, insulin resistance, and skeletal muscle oxidative capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Our study participants performed a similar exercise stress of 5 x 30‐s bouts of quadriceps exercise (total exercise time: 2.5 min), however, at a significantly higher percentage of their peak capacity (65% versus 30%). Slyper and colleagues have also revealed that adiposity, visceral fat volume in particular, is the sole predictor of insulin resistance in obese adolescents ; therefore, it clearly remains a challenge to dissociate the relationship between obesity, insulin resistance, and skeletal muscle oxidative capacity.…”
Section: Discussionmentioning
confidence: 99%
“…The cut‐off for childhood obesity in the USA is ≥95th percentile for gender and age based on the Centers for Disease Control and Prevention growth charts . Paediatric obesity has several negative sequelae including increased risk of diabetes, cardiovascular impairment, musculoskeletal disorders, fatty liver disease and poor quality of life . While family‐based obesity treatment programmes that include a combination of behaviour modification, nutrition education and physical activity have been characterized as the ‘gold standard’ in paediatric obesity treatment, some children do better in these programmes than others .…”
Section: Introductionmentioning
confidence: 99%